Evaluation of distribution strategies for the personal computers industry. - Chua, Hui Hoon. (2008)
This research attempts to determine the most suitable form of distribution strategy for a firm in the PC industry. Two contrasting strategies, the direct distribution and hierarchical strategies are evaluated using a simulation model. Under the conditions set in the model, the results show that the direct distribution strategy has a lower overall cost.